UJI AKTIVITAS EKSTRAK BIJI KAPUK RANDU (Ceiba pentandra Gaertn.) TERHADAP PERILAKU KAWIN TIKUS (Rattus norvegicus) JANTAN - Wirastuti, Dessy Sukma; Wiratmini, Ngurah Intan; Sudirga, Sang Ketut (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
Kapok ( Ceiba pentandra Gaertn.) is one of the plants which has many benefits for the community. This plant is used as a retaining soil from erosion, plant shade, mattress filler material and animal feed. Kapok seed is currently being developed as a herbal contraceptive medicine. The aim of this research is to determine the activity of kapok seed extracts (Ceiba pentandra Gaertn.) on the mating behavior of male rats (Rattus norvegicus). The design used was completely randomized design (CRD) with 4 groups and 8 replications were P0 (distilled water and tween 80), P1 (0,07 mg / kg body weight kapok seed extract), P2 (0,12 mg / kg body weight kapok seed extract), P3 (0,24 mg / kg body weight kapok seed extract). Kapok seed extract treatment is done every day for 33 days, whereas  mating behavior was observed once in 3 days. The parameters observed to assess their mating behavior were the quantity of kissing the vagina, mounting and intromission. The results showed that the kapok seed extract significantly provide a real impact on the mating behavior of male rats which is indicated by a decrease quantity of the kissing vagina, the quantity of mounting andthe quantity of intromission of male rats treated group.